The effectiveness of role-playing technique in improving Thai 7 th graders’ English communication skills - Zaitun Zaitun; Rusnanee Wanyawa (English Language Education Study Program, Teacher Traning and Education Faculty, Universitas Muhammadiyah Cirebon, 2023)
The aims of the study were to determine the effectiveness of Role playing as a technique used in improving students' speaking skills in English communication and report the extent to which this technique was effective. This study applied quantitative methods with a pre-experimental design. One class of 7th graders at Songserm Wittaya School, Thailand, consisting of 30 students, became the sample for the research. The data were collected using a pre- and post-test that measured students' English communication in dialogue, before and after the research. These data were analyzed statistically by using a paired-sample t-test. The findings revealed that the students performed better in the post-test than in the pre-test, in which they reached a mean score of 10.50 in the pre-test and increased to 17.70 in the post-test. Additionally, the significant difference in students’ speaking achievement in pre- and post-tests was indicated by the higher score value compared to t-table. Thus, this research concluded that Role playing used as a technique for improving 7th grade students’ English speaking for communication was effective.Hence, the null hypothesis was rejected. Keywords: English speaking skill, English communication, Role-playing technique